Caspase-11 Mediates Neutrophil Chemotaxis and Extracellular Trap Formation During Acute Gouty Arthritis Through Alteration of Cofilin Phosphorylation - Caution, Kyle; Young, Nicholas; Robledo-Avila, Frank; Krause, Kathrin; Abu Khweek, Arwa; Hamilton, Kaitlin; Badr, Asmaa; Vaidya, Anup; Daily, Kylene; Gosu, Hawin; Anne, Midhun N. K.; Eltobgy, Mostafa; et al. (Frontiers in Immunology, 2019)
Gout is characterized by attacks of arthritis with hyperuricemia and monosodium urate (MSU) crystal-induced inflammation within joints. Innate immune responses are the primary drivers for tissue destruction and inflammation in gout. MSU crystals engage the Nlrp3 inflammasome leading to the activation of caspase-1 and production of IL-1β and IL-18 within gout-affected joints, promoting the influx of neutrophils and monocytes. Here we show that caspase-11-/- mice and their derived macrophages produce significantly reduced levels of gout-specific cytokines including IL-1β, TNFα, IL-6, and KC, while others like IFNγ and IL-12p70 are not altered. IL-1β induces the expression of caspase-11 in an IL-1 receptor-dependent manner in macrophages. In neutrophils, the absence of caspase-11 reduced the ability of neutrophils to migrate in response to exogenously injected KC in vivo. Notably, in vitro, caspase-11-/- neutrophils displayed random migration in response to a KC gradient when compared to their WT counterparts. This phenotype was associated with altered cofilin phosphorylation. Unlike their wild-type counter parts, caspase-11-/- neutrophils also failed to produce neutrophil extracellular traps (NETs) when treated with MSU. Together, this is the first report demonstrating that caspase-11 promotes neutrophil directional trafficking and function in an acute model of gout. Caspase-11 also governs the production of inflammasome-dependent and -independent cytokines from macrophages. Our results offer new, previously unrecognized functions for caspase-11 in macrophages and neutrophils that may apply to other neutrophil-mediated disease conditions besides gout.